Validity, diagnostic accuracy and reliability of the Whispered Paronym Words Test for the Rapid Detection of Presbycusis - Valero-García, Jesús; Vila-Rovira, Josep María (Revista de Investigación en Logopedia, 2022)
The aim of this paper is to determine the validity, diagnostic accuracy and reliability of the Whispered Paronym Words Test (WPWT) when used in detection of presbycusis at primary healthcare centers. The participants were 156 individuals over 65 years of age and 36 young people without hearing problems. Hearing capacity was assessed using pure-tone audiometry and the WPWT.Using the WPWT, 94 people were diagnosed with presbycusis, a finding that significantly correlates with data obtained via pure-tone audiometry [r = -.84 (p
Keywords: Aging; Presbycusis; Screening; Whispered Test